Blockchain-Based Smart Contract: Advancing Digital Consumer Protection and Preventing Private International Law E-Commerce Cases - Tresnawati Tresnawati; Angelina Marlina Fatmawati (Faculty of Law, Universitas Sebelas Maret, 2021)
Blockchain has functioned as a ledger that decentralizes controls with immutable and irreversible character and have the potential to overcome the deficiency of traditional contracts, especially in today’s digital era such as the e-commerce industry. Unfortunately, although famous to be used for blockchain and smart contracts have not been applied widely in Indonesia and there is no regulation that specifically regulates the use of blockchain technology and smart contracts. This article will analyze the application of smart contracts to escalate consumer rights in e-commerce services. This research showed that the self-executory characteristic of smart contracts helps the consumer to have an equal bargaining position with businesses actors in determining the contents of the contract. In response to those curative efforts, the smart contract will be advantageous as a preventive scheme for PIL cases. The self-executory character of the smart contract will prevent many PIL cases which are potentially occurred. The immutable nature of blockchain records will also be helpful for any dispute settlement scheme. This might be led to the tendency that international e-commerce cases should not be litigated or to be set for an arbitration tribunal. Those international e-commerce cases might not require settlement of judicative branch and may be settled at the administrative level. Consequently, this would create a more effective and efficient settlement, both in time and money. Those advantages have made blockchain-based smart contracts will be prospective in Indonesia, in the upcoming future